2023
DOI: 10.3390/ijms242316754
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Antibacterial Scaffolds for the Regeneration of Alveolar Bone in Severe Periodontitis

Konstantinos Theodoridis,
Athanasios S. Arampatzis,
Georgia Liasi
et al.

Abstract: Current clinical treatment of periodontitis alleviates periodontal symptoms and helps to keep the disease under control for extended periods. Despite this, a significant destruction of the tooth’s underlying bone tissue often takes place progressively. Herein, we present a two-way therapeutic approach for local delivery of antibacterial agents and bone tissue regeneration, incorporating ~1% w/w tetracycline hydrochloride (TCH) into a 3D-printed scaffold composed of poly(ε-caprolactone) (PCL). Samples were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Addressing alveolar bone defects and restoring bone structures in patient treatment remains a challenging aspect of clinical practice in dentistry. Nevertheless, significant strides have been taken in incorporating scaffolding and 3D-printing technologies into oral and maxillofacial surgery, particularly in the context of periodontal and alveolar bone regeneration [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and in numerous dental applications [38][39][40]. Studies reported in demonstrate successful applications in periodontal and alveolar bone regeneration, with scaffolding technologies, biodegradable constructs, and antibacterial scaffolds showing promising outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing alveolar bone defects and restoring bone structures in patient treatment remains a challenging aspect of clinical practice in dentistry. Nevertheless, significant strides have been taken in incorporating scaffolding and 3D-printing technologies into oral and maxillofacial surgery, particularly in the context of periodontal and alveolar bone regeneration [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and in numerous dental applications [38][39][40]. Studies reported in demonstrate successful applications in periodontal and alveolar bone regeneration, with scaffolding technologies, biodegradable constructs, and antibacterial scaffolds showing promising outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It allows one to print biocompatible membranes and scaffolds as well as living cells and matrix components in complex 3D functional tissues ( Ma et al, 2019 ). Theodoridis et al ( Theodoridis et al, 2023 ) developed a scaffold based on poly (ε-caprolactone) containing tetracycline hydrochloride; it promoted antimicrobial activity, an organic collagen matrix, and new mineralized bone tissue.…”
mentioning
confidence: 99%